Air Flow Optimization of Discharge Duct based on Peregrine Falcon’s Diving Wing Shape for Forward Curve Centrifugal Blower - Mohd Danial, Ibrahim; M. Z., Mohtar; A. A., Alias; L. K., Wong; Y. S., Yunos; M. R. A., Rahman; A., Zulkharnain; C. S., Tan; R., Thayan (2016)
Centrifugal blowers are one of the largest electrical equipment in Heating, Ventilation and Air Conditioning (HVAC) because it is equipment which is regularly running and contributes to high electrical power consumption. The air flow optimization of a centrifugal blower operated inside a biosafety cabinet (BSC) is the main objective for this paper. Air movement can be accelerated when it passes through an aerodynamic duct inspired from an aerodynamic shape of Peregrine Falcon’s diving flight. The impact of aerodynamic shape to air movement was determined by using computational fluid dynamics (CFD) analysis. Results showed that by introducing this methodology, air velocity discharge improves three times as the ones without any duct modifications. As a conclusion, a novel design of aerodynamic duct shape successfully developed and proved that air velocity can be increase naturally with the same impeller speed or energy consumption. It is a vital design approach in improving BSC designs while increasing its energy efficiency and containment